Redefining Molecular Chaperones as Chaotropes - Macošek, Jakub; Mas, Guillaume; Hiller, Sebastian (Frontiers in Molecular Biosciences, 2021)
Molecular chaperones are the key instruments of bacterial protein homeostasis. Chaperones not only facilitate folding of client proteins, but also transport them, prevent their aggregation, dissolve aggregates and resolve misfolded states. Despite this seemingly large variety, single chaperones can perform several of these functions even on multiple different clients, thus suggesting a single biophysical mechanism underlying. Numerous recently elucidated structures of bacterial chaperone–client complexes show that dynamic interactions between chaperones and their client proteins stabilize conformationally flexible non-native client states, which results in client protein denaturation. Based on these findings, we propose chaotropicity as a suitable biophysical concept to rationalize the generic activity of chaperones. We discuss the consequences of applying this concept in the context of ATP-dependent and -independent chaperones and their functional regulation.